Material properties affecting cutting forces - Bengtsson, Alexander; Johansson, Daniel (My University, 2019)
The aim of this master thesis is to evaluate the feasibility of using readily available material properties to estimate the constants in the proposed models that describe cutting resistance and therefore cutting force. The study is carried out for two types of workpiece materials, each from a different ISO-group. The investigated materials are 316L, an austenitic stainless steel, and 100Cr6, a high carbon through hardening steel. 316L is delivered by two different suppliers while 100Cr6 is delivered in three different hardening conditions, where the latter significantly alters the material characteristics. The study includes characterization of the workpiece materials with activities including grain size estimation, inclusion analysis, tensile testing and hardness testing. Machining experiments are performed using a CNC-lathe and the cutting resistance is calculated based on the measured force response for a certain theoretical chip thickness. The data is generated by using the stepwise increased feed-rate test method. The relation between properties such as hardness and tensile strength with the cutting resistance is presented for the 100Cr6 material. Since there is a connection between the cutting resistance and the cutting force, it is thus feasible to calculate the cutting forces under arbitrary cutting conditions and for different tool geometries. It is also observed that, while the hardening condition of 100Cr6 has a significant effect on its cutting resistance, only a slight difference exists between 316L produced by different suppliers.
Keywords: Cutting forces; cutting resistance; machining; cutting resistance modeling; main cutting force modeling; 316L; 100Cr6; material characterization